Analisis Pemikiran Politik Fundamentalisme Islam Dalam Studi Kasus Gerakan Kelompok Fundamentalis Islam di Indonesia Pasca Era Reformasi - Dandi, Muhammad; Mushthafa A, Hitana; Muzakki R; Juan A, Rendy (Indonesian Democracy Research Center, 2023)
In essence, fundamentalism can appear in any religion and in any country, including Islam in Indonesia. The emergence of the Islamic Fundamentalist movement in Indonesia is an event that is certain to occur, considering that Indonesia is a country with the largest Muslim population in the world. Religious movements that are fundamental and revivalist in nature have become an event that colors the world of politics, social, culture, and the image of contemporary Islam in Indonesia. The emergence of movements from Islamic fundamentalism groups in Indonesia occurred massively after the end of the New Order regime or the reform era. The democratization that has taken place in Indonesia has made it possible for various communities to gather or associate, such as the movement of Islamic fundamentalist groups in Indonesia. The secularization and affiliation of western hegemony in the New Order regime has become a strong assumption for the birth of this group in the reform era. Movements from Islamic Fundamentalism groups in Indonesia during the reform era such as for example, Hizbut Tahrir Indonesia (HTI), the Islamic Defenders Front (FPI), Jemaah Islamiyah (JI), and the Indonesian Mujahidin Council. Therefore, this paper will comprehensively discuss the rationale and characteristics of the Islamic fundamentalist movement, as well as analyze the emergence of Islamic fundamentalist groups in Indonesia during the reform era in order to determine how far the fundamentalist movement has contributed to the harmonization of religious life in Indonesia.